Chapter 8 A Semiotic and Multimodal Analysis of Interactive Relations in Picture Books That Challenge Female Gender Stereotypes - Santamaría- García, Carmen (Taylor & Francis, 2022)
A Semiotic and Multimodal Analysis of Interactive Relations in Picture Books that Challenge Female Gender Stereotypes